2021
DOI: 10.1055/s-0041-1731295
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Global COVID-19 Pandemic on the Incidence, Presentation, and Management of Pediatric Appendicitis: Lessons Learned from the First Wave

Abstract: The fast-evolving nature of the coronavirus disease 2019 (COVID-19) pandemic has led to unprecedented clinical, logistical, and socioeconomical challenges for health-care systems worldwide. While several studies have analyzed the impact on the presentation and management of acute appendicitis (AA) in the adult population, there is a relative paucity of similar research in pediatric patients with AA. To date, there is some evidence that the incidence of simple AA in children may have decreased during the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 99 publications
(138 reference statements)
0
6
0
1
Order By: Relevance
“…Most patients in both groups had ultrasound imaging, but less than half of both groups had CT imaging. The COVID group did demonstrate a significantly delayed presentation regarding the time from SO to ED (36 hours vs 24 [12][13][14][15][16][17][18][19][20][21][22][23][24] hours, P-value = .049). The PAS was also significantly higher in the COVID group (8 [7.5-9] vs 6 [5][6][7], P-value = .003).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Most patients in both groups had ultrasound imaging, but less than half of both groups had CT imaging. The COVID group did demonstrate a significantly delayed presentation regarding the time from SO to ED (36 hours vs 24 [12][13][14][15][16][17][18][19][20][21][22][23][24] hours, P-value = .049). The PAS was also significantly higher in the COVID group (8 [7.5-9] vs 6 [5][6][7], P-value = .003).…”
Section: Resultsmentioning
confidence: 89%
“…These findings align with several studies demonstrating no worse postoperative complications for pediatric acute appendicitis during the COVID-19 pandemic. 12,14 However, one other pediatric study identified worse outcomes. 13 This variance in findings requires that further validation be implemented to better understand and improve the clinical outcomes moving forward.…”
Section: Discussionmentioning
confidence: 99%
“…Failure to access life-saving treatments can increase the severity of the disease, causing complications and even death [ 6 ]. During the COVID-19 pandemic, changes in the diagnosis and treatment results for abdominal pain requiring surgery, such as acute appendicitis, and even changes in treatment trends, have been actively reported [ 7 , 8 , 9 , 10 , 11 , 12 ]. On the other hand, there have been few reports of intussusceptions in pediatric patients.…”
Section: Introductionmentioning
confidence: 99%
“…Since the outbreak of COVID-19, this epidemic has brought about widespread restrictions on socializing, travel, business, education, and healthcare. The compulsory strategies to prevent the spread of COVID-19 by both countries and hospitals, as well as the fear of exposure and risk of infection for patients themselves [ 4 ], has changed the epidemiology of various diseases, such as bronchiolitis and asthma [ 5 ], seasonal influenza [ 6 ], acute appendicitis [ 7 ], etc. As for intussusception for pediatric patients, Zheng et al in China were the first to report that the COVID-19 pandemic and its resultant quarantine strategies have significantly reduced the incidence of intussusception [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In order to prevent further spread of this epidemic, many countries have carried out a series of compulsory strategies, such as wearing face masks and checking temperatures in public, cancelling large gatherings, mass testing for SARS-CoV-2, closing schools and public places, and implementing social and physical distancing and even lockdowns. Together with the fear of exposure and risk of infection for patients themselves [ 4 ], these preventative measures have resulted in a global decline, owing to the number of emergency department (ED) visits and hospitalizations of many diseases [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%